2018
DOI: 10.1111/jre.12569
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biodegradable poly(lactic‐co‐glycolic acid)‐based microspheres loaded with quercetin on stemness, viability and osteogenic differentiation potential of stem cell spheroids

Abstract: Biodegradable microspheres loaded with quercetin produced prolonged release profiles with increased mineralization. Microspheres loaded with quercetin can be used for the enhancement of osteoblastic differentiation in cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Comparably, the incorporation of quercetin into biodegradable materials, hydroxyapatite, transition metals or graphene oxide produced anabolic effects via the upregulation of osteogenic genes. Biodegradable poly(lactic-co-glycolic acid)-based microspheres loaded with 1 µg/mL quercetin raised ALP, COL1 and Runx-2 expression in stem-cell spheroids cultured in osteogenic medium [72]. Song and co-authors found that two types of three-dimensional bone scaffold (quercetin/silk fibroin/hydroxyapatite scaffold and quercetin/duck's foot collagen/hydroxyapatite sponge) enhanced osteogenesis, determined by increases in MSCs' growth and proliferation, ALP, COL1, osteocalcin and Runx-2 [47,48].…”
Section: The Effects Of Quercetin On Osteoblastogenesismentioning
confidence: 98%
See 2 more Smart Citations
“…Comparably, the incorporation of quercetin into biodegradable materials, hydroxyapatite, transition metals or graphene oxide produced anabolic effects via the upregulation of osteogenic genes. Biodegradable poly(lactic-co-glycolic acid)-based microspheres loaded with 1 µg/mL quercetin raised ALP, COL1 and Runx-2 expression in stem-cell spheroids cultured in osteogenic medium [72]. Song and co-authors found that two types of three-dimensional bone scaffold (quercetin/silk fibroin/hydroxyapatite scaffold and quercetin/duck's foot collagen/hydroxyapatite sponge) enhanced osteogenesis, determined by increases in MSCs' growth and proliferation, ALP, COL1, osteocalcin and Runx-2 [47,48].…”
Section: The Effects Of Quercetin On Osteoblastogenesismentioning
confidence: 98%
“…Recently, Lee and colleagues fabricated three-dimensional stem-cell spheroids (containing gingiva-derived stem cells and MC3T3-E1 cells) and cultured them in osteogenic medium in the presence of quercetin at the concentration of 1 µg/mL. Quercetin resulted in significant increases in ALP activity and Runx-2 expression [72]. Human osteoblast-like MG-63 cells grown in medium containing ethanolic fraction of Cissus quadrangularis enriched with rutin (65.36 ± 0.75 mg/g) and quercetin (1.06 ± 0.12 mg/g) also displayed higher ALP levels [73].…”
Section: The Effects Of Quercetin On Osteoblastogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffold porosity, topography, mechanical properties, and drug delivery capacity all serve as important variables when designing such scaffolds. Both PLGA microspheres and electrospun nanofibers have also been used for differentiating stem cells into mature tissue types as well [210,211]. Intriguingly, despite its widespread adoption as a biomaterial for clinical applications as well as for engineering tissues in vitro, PLGA has not been adopted as a bioink for use with 3D printers.…”
Section: Poly (Lactic-co-glycolic Acid)mentioning
confidence: 99%
“…In addition, the percentages of polychrome sequential fluorescence labeling of new mineralized tissue in the quercetin-loaded nHA group were significantly higher than those in the nHA group, and more newly formed bone tissue penetrated into the top of the defect of the quercetin-loaded nHA group, whereas only limited new bone formation was shown on the bottom of the defect of the nHA group by V-G picro fuchsin (Zhou et al, 2017). Quercetinloaded biodegradable PLGA microspheres had prolonged release profiles without burst drug release and resulted in enhanced osteogenic differentiation and mineralization of stem cell spheroids according to ALP assays, ARS staining, and RT-PCR (Lee et al, 2018).…”
Section: Quercetinmentioning
confidence: 97%